The Effect of Interhospital Transfers on the Outcome of Rural Trauma. Issue 1 (January 2017) - Wild, Jeffrey; Younus, Jabran M.; Malekpour, Mahdi; Neuhaus, Nina; Widom, Kenneth; Rapp, Megan; Leonard, Diane; Baro, Susan; Dove, James; Hunsinger, Marie; Blansfield, Joseph; Shabahang, Mohsen; et al.
Urban areas house the majority of the population in the United States but trauma deaths occur more commonly in rural areas. In this study, we aimed to investigate if direct patient admission to a Level I trauma center improves outcomes in rural trauma. We retrospectively reviewed data in our trauma database from January 2008 to the end of December 2012 to compare the overall outcomes between direct admissions (DAs) and interhospital transfers (IHTs). Of the 6118 patients who met the inclusion criteria, 59.5 per cent were in the DA group and 40.5 per cent in the IHT group. Injury severity score was similar between the two groups but severe traumatic brain injury was more common (P = 0.001) in the DA group. Hospital length of stay, complication rate, and in-hospital mortality were not different between the two groups (all P > 0.2). In multivariate analysis, there was no difference in survival between the two modes of admission (odds ratio, 95% confidence interval: 0.91, 0.69–1.20, P = 0.51). We concluded that rural trauma IHTs had no detrimental impact on the outcome. Prospective studies would better elucidate factors associated with patient outcomes in rural trauma.